Answer:
(- 6, 0 )
Step-by-step explanation:
Given the 2 equations
3x + 2y = - 18 → (1)
2x + 9y = - 12 → (2)
Multiplying (1) by 2 and (2) by - 3 and adding will eliminate the term in x, that is
6x + 4y = - 36 → (3)
- 6x - 27y = 36 → (4)
Add (3) and (4) term by term to eliminate x
- 23y = 0
y = 0
Substitute y = 0 into either of the 2 equations and evaluate for x
Substituting into (1)
3x + 0 = - 18
3x = - 18 ( divide both sides by 3 )
x = - 6
Solution is (- 6, 0 )
-6a-5=-95 Given
-6(15)-5=-95 Substitution
a=15 idk the reason im not real good at this but i tried!
Hope you have a nice day
<span><span>Solve the system for x and y.</span><span>2y = x + 8</span><span>2y − 10 = 2x</span> <span>A) x = </span>−<span>3, y = 2</span> <span>B) x = </span>−<span>2, y = 3</span> <span>C) x = </span>−<span>5, y = 2</span> <span>D) x = 0, y = -5</span></span>
Answer:
y = - 3x - 7
Step-by-step explanation:
The equation of a line in slope- intercept form is
y = mx + c ( m is the slope and c the y- intercept )
Here m = - 3, then
y = - 3x + c ← is the partial equation
To find c substitute (- 2, - 1) into the partial equation
- 1 = 6 + c ⇒ c = - 1 - 6 = - 7
y = - 3x - 7 ← equation of line